Utillization of Green Betel Leaves (Piper betle L) as Traditional Medicine for Local Commununities in Serang Jaya Hilir Village, Pematang Jaya, Langkat: Pemanfaatan Daun Sirih Hijau (Piper betle L) Sebagai Obat Tradisional Bagi Masyarakat Lokal di Desa Serang Jaya Hilir, Pematang Jaya, Langkat - Nur, Ulfatun; Suwardi, Adi Bejo (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2025)
Indonesia is a center of biodiversity, including the green betel plant (Piper betle L) which has long been used in traditional traditions and medicine. This study aims to identify the use of green betel leaves, the types of diseases treated and the processing methods as traditional medicine by local people in Serang Jaya Hilir Village, Pematang Jaya District, Langkat Regency. The study was conducted in four hamlets of Serang Jaya Hilir Village with a qualitative research type using a quantitative descriptive method. In this study, the selection of respondents was carried out using the purposive sampling method, meaning that the data taken was based on community understanding related to the use of green betel leaves as traditional medicine, consisting of 10 respondents. The data is presented in the form of tables and graphs with data collection techniques in the form of observation, interviews, and documentation. The results of the study showed that people use green betel leaves to treat 10 types of diseases, including vaginal discharge, eye irritation, itching, bad breath, body odor, toothache, stomachache, cough, strengthening teeth, and nosebleeds. The method of processing and using betel leaves varies according to the type of disease, such as boiling, chewing, pounding, or rolling. Leucorrhea is the most frequently mentioned complaint, indicating public trust in the effectiveness of green betel leaves in traditional medicine. This study is important as education regarding the safe use and preservation of green betel leaf resources so that they remain sustainable. Suggestions, the need for further scientific studies on the active content, and side effects of green betel leaves, as well as innovation of processed products so that their use is safer and wider.